Períodos de interferência de plantas daninhas na cultura do girassol - da Silva, José Iran Cardoso; Martins, Dagoberto [UNESP]; Pereira, Maria Renata Rocha; Cardoso, Leonildo Alves; Rodrigues-Costa, Andreia Cristina Peres (My University, 2013)
The interference of weeds in sunflower cultivation can significantly reduce the productivity of achenes. The objective of this study was to determine the period before interference and total period of interference of the weed community on productivity and achene oil of sunflower cultivation. The experiment was conducted under field conditions in the fieldin Botucatu (SP) in the 2007/2008 agricultural year. The experimental design was a randomized complete block with four replications. The treatments were composed of portions represent periods of control and presence of weeds. For control periods, the culture was kept free of weeds by increasing periods of 7, 14, 21, 28, 35, 42, 49 and 110 days after the emergence (DAE) of sunflower. For periods of coexistence, the culture was maintained in the presence of the weed community for the same periods. We assessed the following variables: diameter of chapters, achene yield, oil yield of sunflower, density and dry matter of weeds and phytosociological indices. The period before the interference was 35 DAE culture to the productivity of achenes, and the total period of interference lasted until 24 DAE. For oil yield, the period before the interference was 25 DAE, whereas the total period of interference lasted for 14 DAE.

A interferência de plantas daninhas na cultura do girassol pode reduzir significativamente a produtividade de aquênios. O objetivo deste trabalho foi determinar o Período Anterior à Interferência e o Período Total de Prevenção à Interferência da comunidade infestante sobre a produtividade de aquênios e de óleo da cultura do girassol. O experimento foi conduzido em campo, na área da Faculdade de Ciências Agronômicas FCA/UNESP, na Fazenda Experimental Lageado, município de Botucatu (SP), no ano agrícola de 2007/2008. O delineamento experimental foi o de blocos casualizados, com quatro repetições. Os tratamentos foram compostos por parcelas constituídas por períodos de controle e de presença de plantas daninhas. Para os períodos de controle, a cultura foi mantida livre das plantas daninhas pelos períodos crescentes de 7, 14, 21, 28, 35, 42, 49 e 110 dias após a emergência do girassol. Para os períodos de convivência, a cultura foi mantida na presença da comunidade infestante pelos mesmos períodos. Foram avaliadas as seguintes variáveis: Diâmetro de capítulos, produtividade de aquênios, rendimento de óleo de girassol, densidade e matéria seca das plantas daninhas e índices fitossociológicos. O período anterior à interferência foi de 35 DAE da cultura para a produtividade de aquênios, sendo que o período total de prevenção à interferência estendeu-se até 24 DAE. Para o rendimento de óleo, o período anterior à interferência foi de 25 DAE, enquanto que o período total de prevenção à interferência prolongou-se por 14 DAE.
Periods of weed interference in sunflower culture
Keywords: Helianthus annuus; Weed competition; Weeds